2014
DOI: 10.1039/c4ay00086b
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional nanogold microsphere doped with Prussian blue nanoparticles for sensitive electrochemical immunoassay of cancer marker

Abstract: A novel signal-amplified strategy for sensitive electrochemical immunoassay of cancer marker was developed by using Prussian blue nanoparticles-doped nanogold microsphere as the promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A standard practice for biosensors is to amplify the signal as a means of increasing the sensitivity. To achieve this, different strategies have been suggested, such as nanoparticles, magnetic particles, nanomaterials, enzymes, artificial enzymes, and fluorescence [11,[52][53][54][55][56]. In this work, we made use of AuNP conjugates to amplify the steady-state current, as depicted in Figure 6a.…”
Section: Electrochemical Signal Amplification Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…A standard practice for biosensors is to amplify the signal as a means of increasing the sensitivity. To achieve this, different strategies have been suggested, such as nanoparticles, magnetic particles, nanomaterials, enzymes, artificial enzymes, and fluorescence [11,[52][53][54][55][56]. In this work, we made use of AuNP conjugates to amplify the steady-state current, as depicted in Figure 6a.…”
Section: Electrochemical Signal Amplification Strategymentioning
confidence: 99%
“…An important advantage of this approach is that existing ELISA assays can be transferred to an electrochemical platform, assuming that a suitable electroactive substrate and detection technique are in place. Furthermore, HRP, as a label, offers multiple advantages due its robustness, relatively small size, inexpensiveness, high turnover rate, and compatibility with a large variety of electroactive substrates [11][12][13][14][15]. On the other hand, EIS sensors can operate label-free and involve an external redox probe, usually ferro/ferricyanide or ferrocene, present in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the multifunctional HPBNPs could be useful as promising theranostic nanomedicine (noninvasive imaging and remote-controlled therapy) in the near future [9]. Li et al reported the development of a strategy for sensitive electrochemical immunoassay of human tissue polypeptide antigen, cancer marker using future science group Prussian blue nanoparticles & their analogues for application to cancer theranostics Editorial Prussian blue nanoparticles-doped nanogold microsphere (AuPB) as promoter [20]. The electrochemical immunoassay shows nice electrochemical responses for the detection of tissue polypeptide antigen at low concentration range (5 pg ml -1 ).…”
Section: Theranostic Applications Of Prussian Blue Nanoparticles and Their Analoguesmentioning
confidence: 99%
“…Over the past decades, Prussian blue (PB) has attracted more and more scientific interest in electrochemical sensing field because of their excellent catalytic ability, good biocompatibility, high selectivity and stability. In phosphate buffer saline (PBS), PB can result in redox reactions and give high electric signal in electrochemical detection process.And thus, PB can be used both as a platform and a signal reporter [23–24]. In order to bind easily with aptamers and achieve high electric signal, Au NPs could be used [25, 26].…”
Section: Introductionmentioning
confidence: 99%